2006
DOI: 10.1007/11861461_25
|View full text |Cite
|
Sign up to set email alerts
|

Using Verbs to Characterize Noun-Noun Relations

Abstract: Abstract. We present a novel, simple, unsupervised method for characterizing the semantic relations that hold between nouns in noun-noun compounds. The main idea is to discover predicates that make explicit the hidden relations between the nouns. This is accomplished by writing Web search engine queries that restate the noun compound as a relative clause containing a wildcard character to be filled in with a verb. A comparison to results from the literature suggest this is a promising approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…We built such Google queries manually, starting with the patterns proposed by Hearst (1992) and Nakov and Hearst (2006). For example, instances of CONTENT-CONTAINER come up in response to queries such as ''* contains *'', ''* holds *'', ''the * in the *''.…”
Section: Building the Annotated Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…We built such Google queries manually, starting with the patterns proposed by Hearst (1992) and Nakov and Hearst (2006). For example, instances of CONTENT-CONTAINER come up in response to queries such as ''* contains *'', ''* holds *'', ''the * in the *''.…”
Section: Building the Annotated Data Setsmentioning
confidence: 99%
“…The literature shows a wide variety of methods of nominal relation classification (Lapata 2002;Moldovan et al 2004;Lapata and Keller 2005;Girju et al 2005;Kim and Baldwin 2005;Nakov and Hearst 2006;Nastase et al 2006;Pantel and Pennacchiotti 2006;Pennacchiotti and Pantel 2006;Turney 2005). They depend as much on the training data as on the domain of application and the available resources.…”
Section: Introductionmentioning
confidence: 97%
“…As previously mentioned, NCs designating processes all have underlying propositions. Nakov and Hearst (2006) confirmed that verb paraphrases are useful for disambiguating these compound terms and eliciting their meaning. Thus, in order to access the concordances that allude to the semantics of the MWT in question, we not only downloaded the concordance lines where the NC appeared but also the concordances where paraphrases had been used (see Figure 1).…”
Section: Methodsmentioning
confidence: 56%
“…There have been two general lines of research: the first one derives the noun compound semantics from the semantics of the nouns it is made of [Rosario et al 2002;Moldovan et al 2004;Kim and Baldwin 2005;Tratz and Hovy 2010], while the second one models the relationship between the nouns directly [Vanderwende 1994;Lapata 2002;Kim and Baldwin 2006;Nakov and Hearst 2006;Butnariu and Veale 2008].…”
Section: Noun Compounds In Computational Linguisticsmentioning
confidence: 99%